Synergism between cAMP and PPARγ Signalling in the Initiation of UCP1 Gene Expression in HIB1B Brown Adipocytes - H. Y. Chen; Q. Liu; A. M. Salter; M. A. Lomax (PPAR Research)
Expression of the brown adipocyte-specific gene, uncoupling protein 1 (UCP1), is increased by both PPARγ stimulation and cAMP activation through their ability to stimulate the expression of the PPAR coactivator PGC1α. In HIB1B brown preadipocytes, combination of the PPARγ agonist, rosiglitazone, and the cAMP stimulator forskolin synergistically increased UCP1 mRNA expression, but PGC1α expression was only increased additively by the two drugs. The PPARγ antagonist, GW9662, and the PKA inhibitor, H89, both inhibited UCP1 expression stimulated by rosiglitazone and forskolin but PGC1α expression was not altered to the same extent. Reporter studies demonstrated that combined rosiglitazone and forskolin synergistically activated transcription from a full length 3.1 kbp UCP1 luciferase promoter construct, but the response was only additive and much reduced when a minimal 260 bp proximal UCP1 promoter was examined. Rosiglitazone and forskolin in combination were able to synergistically stimulate promoters comprising of tandem repeats of either PPREs or CREs. We conclude that rosiglitazone and forskolin act together to synergistically activate the UCP1 promoter directly rather than by increasing PGC1α expression and by a mechanism involving cross-talk between the signalling systems regulating the CRE and PPRE on the promoters.